A Comparison of Contemporary Clinical Outcomes Following Femoro-Popliteal Plain Balloon Angioplasty and Bypass Surgery for Chronic Limb Threatening Ischemia. (August 2021) - Meecham, Lewis; Popplewell, Mathew A.; Bate, Gareth R.; Patel, Smitaa; Bradbury, Andrew W.
Introduction: Despite the BASIL-1 trial concluding that bypass surgery (BS) was superior to plain balloon angioplasty (PBA) in terms of longer-term amputation free (AFS) and overall survival (OS), CLTI patients are increasingly offered an endovascular-first revascularization strategy. This study investigates whether the results of BASIL-1 are still relevant to current practice by comparing femoro-popliteal (FP) BS with PBA in a series of CLTI patients treated in our unit 10 years after BASIL-1 (1999-2004). Methods: We retrospectively analyzed prospectively gathered hospital data pertaining to 279 patients undergoing primary FP BS or PBA for CLTI in the period 2009 to 2014. We report baseline characteristics, 30-day morbidity and mortality, major adverse cardiovascular events (MACE) and long-term AFS, limb salvage (LS), OS, major adverse limb events (MALE), and freedom from re-intervention (FFR). Results: 234 (84%) and 45 (16%) patients underwent PBA and BS respectively. PBA patients were significantly older (77 vs 71 years, P = 0.001) and more likely to be female (45% vs 28%, P = 0.026). Bollinger and GLASS anatomic scores were significantly more severe in the BS group. Technical success was better for BS (100% vs 87%, P = 0.007). Index hospital stay was shorter for PBA (9.1 vs 15.6 days, P = 0.035) but there was no difference in hospital days or admissions over the next 12 months. AFS (HR 1.00), LS (HR 1.44), OS (HR 0.81), MALE (HR 1.25) and FFR (HR = 1.00) were not significantly different between PBA and BS. Conclusion: Important clinical outcomes following FP BS and PBA for CLTI have not changed significantly in our unit in the 10 years following the BASIL-1 trial. BASIL-1 therefore remains relevant to our current practice and should inform our approach to the management of CLTI going forward.